Hyperthermic intraperitoneal chemotherapy in ovarian cancer: a comprehensive review - Li, Yan; Xu, Xiuxiu (Frontiers in Oncology, 2026)
Hyperthermic intraperitoneal chemotherapy (HIPEC) is increasingly recognized as a valuable adjunct to cytoreductive surgery (CRS) in the management of ovarian cancer with peritoneal dissemination. This comprehensive review synthesizes contemporary evidence on the efficacy, safety, and future directions of HIPEC across various clinical settings, including primary, interval, and recurrent disease. Landmark studies such as the OVHIPEC-1 trial have demonstrated significant survival benefits when HIPEC is integrated into interval cytoreductive surgery following neoadjuvant chemotherapy, with improvements in both progression-free and overall survival without increasing severe morbidity. Survival gains have also been observed in upfront settings, particularly in patients with stage III epithelial ovarian cancer. However, evidence in recurrent disease remains mixed, with some trials showing benefit and others showing no significant advantage. Critical to the success of HIPEC are optimal patient selection and surgical quality, with completeness of cytoreduction (CC0/CC1), low peritoneal cancer index (PCI), and biological factors such as tumor microenvironment composition emerging as key prognostic indicators. Although HIPEC is associated with a higher incidence of grade 3–5 adverse events, particularly renal and gastrointestinal toxicities, these are generally manageable in experienced centers. Enhanced recovery protocols and careful perioperative management have further improved safety profiles. Emerging innovations include combination with normothermic intraperitoneal chemotherapy, integration of immunotherapy such as intraperitoneal nivolumab, use of paclitaxel-based regimens, and exploration of minimally invasive techniques. Future directions also involve molecular profiling, AI-driven patient selection, and synergy with targeted therapies like PARP inhibitors. Ongoing research is essential to refine protocols, standardize patient selection, and integrate HIPEC into evolving systemic treatment landscapes. In conclusion, HIPEC represents a major advancement in the multimodal treatment of advanced ovarian cancer, offering meaningful survival benefits when applied in selected patients by multidisciplinary teams.